2015
DOI: 10.1007/s00404-015-3774-2
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic changes of vaginal microecosystem in patients with recurrent vulvovaginal candidiasis: a retrospective study of 800 patients

Abstract: There were vaginal microecological imbalances in all developing stages of RVVC. As for vaginal flora, diverse sorts changed to normal Lactobacillus dominantly with the development of RVVC. In the first occurrence of RVVC, after antifungal treatment, Lactobacillus is suggested to be timely supplemented to restore vaginal microecological balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…The persistence of vaginal dysbacteriosis is thought to promote gynecological cancer. 7 , 27 A decline in the quantity and activity of Lactobacillus leads to an overgrowth of anaerobic bacteria. 28 Deleterious metabolites such as nitrous acid can be produced by these organisms, and the risk of HPV infection also increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence of vaginal dysbacteriosis is thought to promote gynecological cancer. 7 , 27 A decline in the quantity and activity of Lactobacillus leads to an overgrowth of anaerobic bacteria. 28 Deleterious metabolites such as nitrous acid can be produced by these organisms, and the risk of HPV infection also increases.…”
Section: Discussionmentioning
confidence: 99%
“… 6 The bacteria in the vagina maintain a dynamic balance under physiological conditions, but the imbalance of vaginal flora leads to multiple gynecological diseases, such as coleitis, high-grade cervical intraepithelial neoplasia (CIN), and cervical cancer. 7 It has been confirmed that Gardnerella and Monilia are the main bacteria that induce coleitis. 8 , 9 Previous research has shown that the abundance of vaginal flora such as Mycoplasma genitalium , 10 aerobic lactobacilli, Staphylococcus epidermidis , Enterococci, Escherichia coli , and Bacteriodes species 11 in patients with cervical cancer is different from that in healthy controls.…”
Section: Introductionmentioning
confidence: 95%
“…Laboratory tests for genital tract infection including Trichomonas in vaginal secretions were confirmed by wet mount. Gram staining of vaginal secretions for vaginal cleanliness [16] and detection of hyphae and spores of Candida and clue cells [17] were performed. Gram staining of cervical secretions for detection of NG and leukocytes was also conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Wet preparations of vaginal swab samples that are examined microscopically and stained by Gram staining are investigated using the VMES. [4] This tool is mainly composed of morphological and functional microecological indicators. [4] The former diagnostic modality includes bacterial density, flora diversity, dominant bacterial flora, indicators of inflammation [such as white blood cell (WBC) count], and pathogenic microorganisms.…”
Section: What Is the Vaginal Microecology Evaluation System?mentioning
confidence: 99%
“…A multicenter epidemiological study used the Vaginal Microecology Evaluation System (VMES) as a tool to analyze the vaginal microbiomes in most areas of China. [4] The aim of this article is to introduce knowledge on changes to the vaginal microecological environment and inform users of the VMES in diagnosing and managing the broad range of vaginal infections that can occur.…”
Section: Introductionmentioning
confidence: 99%